Construction technology for tall buildings - Chew, Michael Yit Lin (World Scientific Co.Pte.Ltd., 2012)
Introduces the advanced construction practices and processes for tall buildings from foundation to roof. This title presents the methods, materials, equipment and systems used for the construction of tall buildings